Bayesian inference for heterogeneous caprock permeability based on above zone pressure monitoring. (February 2017) - Namhata, Argha; Small, Mitchell J.; Dilmore, Robert M.; Nakles, David V.; King, Seth
Highlights: The uncertainty of above zone pressure measurements at CO2 storage site is estimated. A Bayesian approach is used to infer different caprock fracture scenarios. Measurement error is included in estimating the likelihood function. Results can be used for optimized design of pressure based monitoring system. Abstract: The presence of faults/fractures or highly permeable zones in the primary sealing caprock of a CO2 storage reservoir can result in leakage of CO2 . Monitoring of leakage requires the capability to detect and resolve the onset, location, and volume of leakage in a systematic and timely manner. Pressure-based monitoring possesses such capabilities. This study demonstrates a basis for monitoring network design based on the characterization of CO2 leakage scenarios through an assessment of the integrity and permeability of the caprock inferred from above zone pressure measurements. Four representative heterogeneous fractured seal types are characterized to demonstrate seal permeability ranging from highly permeable to impermeable. Based on Bayesian classification theory, the probability of each fractured caprock scenario given above zone pressure measurements with measurement error is inferred. The sensitivity to injection rate and caprock thickness is also evaluated and the probability of proper classification is calculated. The time required to distinguish between above zone pressure outcomes and the associated leakage scenarios is also computed.